Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fpsyt.2022.930121
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Cognitive Screening in Asian Patients With Heart Failure: A Systematic Review

Abstract: BackgroundThe prevalence of undiagnosed cognitive impairment in patients with heart failure is alarmingly high in Asia. There is still no consensus on cognitive screening tools to detect cognitive impairment in the Asian heart failure population. The clinical implications based on our systematic review may help to improve cognitive screening practice for patients with heart failure in Asia.MethodsThis review is registered in the PROSPERO (CRD42021264288). Using the Preferred Reporting Items for Systematic Revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
1
0
Order By: Relevance
“…Several neuropsychological tests for evaluating cognitive function are available, but none of these have been particularly developed for AHF patients [ 23 ]. A recent systematic review found that several brief cognitive tests, such as the Montreal Cognitive Assessment (MoCA), Mini-Mental Statement Examination (MMSE), and Mini-Cog, were used to screen the Asian HF population [ 24 ]. The LNNB-S is a neuropsychological assessment battery designed to screen for cognitive impairment in various diseases [ 11 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several neuropsychological tests for evaluating cognitive function are available, but none of these have been particularly developed for AHF patients [ 23 ]. A recent systematic review found that several brief cognitive tests, such as the Montreal Cognitive Assessment (MoCA), Mini-Mental Statement Examination (MMSE), and Mini-Cog, were used to screen the Asian HF population [ 24 ]. The LNNB-S is a neuropsychological assessment battery designed to screen for cognitive impairment in various diseases [ 11 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Short cognitive tests, such as the Montreal Cognitive Assessment (MoCA), the Mini-Cog, and the Mini-Mental State Examination (MMSE), have been used to screen global cognitive function among Asian patients with HF. However, insufficient information is available to compare the reliability of these short cognitive screening tests to a formal, gold-standard neuropsychological evaluation for patients with HF in Asia (Niu et al, 2022 ). Therefore, it is vital to identify the instruments that can be used to assess cognitive function among patients with HF.…”
Section: Introductionmentioning
confidence: 99%
“…However, memory deficits are common and significantly hinder effective self-care management in patients with HF (Toledo et al, 2019). A system review revealed that HF patients with memory deficits were more likely to report inadequate self-care (Niu et al, 2022). For instance, patients could have difficulty identifying the aggravation of symptoms, making appropriate decisions about their disease, and following medical advice.…”
Section: Introductionmentioning
confidence: 99%